ANALISIS KARAKTER GEMAR MEMBACA TERHADAP KEMAMPUAN LITERASI DIGITAL SISWA SMP - Uswatun Hasanah; Islamiani Safitri; Risma Delima Harahap (STKIP Siliwangi, 2023)
The background of this research is to know and describe the character values ​​of interest in reading and digital literacy abilities of junior high school students. Character education for fond of reading is education that raises students' awareness to carry out reading activities by seeking information from various sources, including digital. This research aims to analyze and describe the character of reading and digital literacy skills of students. This research method uses a descriptive approach with a quantitative method by assessing the character of liking to read and digital literacy skills with a total of 150 student respondents. Data obtained with a questionnaire instrument. The written questionnaire instrument consists of 10 questions for characters who like to read and 10 questions for digital literacy skills using the Guttman scale. Data analysis techniques with descriptive statistics. The results showed that the character value of interest in reading from the six classes obtained an average proportion value of 75.05% in the good category. Meanwhile, the digital literacy abilities of the six classes obtained an average proportion score of 83.09% in the very good category. This shows that the reading character value has a positive relationship to the value of students' digital abilities.